Wear behaviour of Fe/M7C3 metal matrix composites with various microstructures during dry sliding - Yilmaz, O; Aksoy, M; Yidirim, S (Maney Publishing, 2003)
The wear mechanisms of iron based metal matrix composites and the wear behaviours of various microstructures were systematically studied by dry sliding wear testing and SEM examination. The experimental results show that three dominant wear mechanisms appeared in succession with increasing normal load during dry sliding. The transition of the wear mechanisms depended mainly upon the conditions of testing, and additionally it was seen that changes in microstructure of the steel had no marked effect on the transition. In the case of mild wear, no obvious differences in wear volume were found for the various microstructures. However, considerable differences in the wear volumes were observed under conditions of severe wear characterised by adhesion and delamination. The experimental results also indicate that the differences in wear resistance of the various microstructures were caused by differences in microstructural thermal stability, resistance to plastic deformation, resistance to nucleation and propagation of microcracks and especially by differences in energy consumption in these layers during wear.
Keywords: Abrasive Wear; Particle Composites; Aluminum-Alloys; Steel; Fabrication; Resistance